Coronary microvascular dysfunction as assessed by angiography-derived index of microvascular resistance co-localizes with and may explain the presence of ischemia in stress-cardiac magnetic resonance imaging in the absence of coronary artery disease - Milzi, Andrea; Dettori, Rosalia; Lubberich, Richard Karl; Burgmaier, Kathrin; Marx, Nikolaus; Reith, Sebastian; Burgmaier, Mathias (Frontiers in Cardiovascular Medicine, 2022)
Introduction Ischemia with no obstructive coronary disease (INOCA) is a frequent phenomenon in the cath lab. A possible cause is coronary microvascular dysfunction (CMD), which may be assessed by invasive testing with possible complications; therefore, less invasive approaches have emerged, such as the angiography-derived index of microvascular resistance (aIMR). The aim of our study was to investigate the association of single-vessel aIMR as a measure of CMD with areas of INOCA in stress testing. Methods We measured aIMR in 286 vessels from 102 patients undergoing both stress cMRI and coronary angiography. Groups were (a) INOCA group (93 vessels, 32 patients); (b) coronary artery disease (CAD) control group (116 vessels, 42 patients) with ischemia due to relevant stenosis; and (c) control group (77 vessels, 28 patients) without ischemia or relevant stenosis. Results INOCA patients presented higher mean aIMR (28.3 ± 5.7) compared to both CAD patients (17.4 ± 5.7, p < 0.001) and controls (22.1 ± 5.9, p < 0.001). Furthermore, in INOCA patients aIMR was significantly increased (33.0 ± 8.1 vs. 25.8 ± 6.3, p = 0.021) in vessels with vs. without ischemia. Single vessel aIMR presented a very good diagnostic efficiency in detecting INOCA [AUC 0.865 (0.804–0.925), optimal cut-off 27.1, p < 0.001]. Conclusion CMD, as assessed by 3-vessel aIMR, co-localizes with and may explain the presence of ischemia in stress-cMRI in INOCA.